Dinamika Terjemah Al-Qur'an (Studi Perbandingan Terjemah Al-Qur'an Kemenerian Agama RI dan Muhammad Thalib) - Muhammad, Muhammad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2018)
This paper compares two translations of the Qur’an: Al-Quran dan Terjemahnya by the team of the Ministry of Religious Affairs/MORA and Al-Quran Tarjamah Tafsiriyah by Muhammad Thalib. Scholars argue differently as to whether the Qur’an is translatable or not. Several classical and contemporary scholars argue that translating the Qur’an is forbidden (haram), while others allow it. Muhammad Thalib claims that Al-Quran dan Terjemahnya includes literal (harfiyah) translation, which is forbidden by scholars, and contains 3400 errors. On that basis, he composed Al-Quran Tarjamah Tafsiriyah as a correction of the former translation. I compare Al-Quran dan Terjemahnya’s translations of several verses on theological doctrine, syari’ah and mu’amalah, of which Thalib considers as containing errors, and those of Thalib’s translation himself to look for similarities and differences. The research shows that there is no significant difference between the two translations. The difference was limited to their respective method and purpose. MORA’s translation was oriented to translate the Qur’an faithfully, while Muhammad Thalib’s translation was oriented to provide an interpretive translation. For some verses, Thalib’s translation provides clearer meaning than that MORA’s. I argue that while translation errors are found in Thalib’s translation, none is found in MORA’s translation.Key words: Al-Quran Terjemahnya, Tarjamah Tafsiriyah, comparison, strength, weakness.